Preparation of Tragopogon graminifolius-loaded electrospun nanofibers and evaluating its wound healing activity in a rat model of skin scar - Almasi, Leila; Arkan, Elham; Farzaei, Mohammad Hosein; Iranpanah, Amin; Jalili, Cyrus; Abbaszadeh, Fatemeh; Aghaz, Faranak; Fakhri, Sajad; Echeverría, Javier (Frontiers in Pharmacology, 2025)
BackgroundGrowing reports are dedicated to providing novel agents for wound healing with fewer adverse effects and higher efficacy. The efficacy of nanofibers composed of polyvinyl alcohol (PVA)/polyethylene oxide (PEO)/chitosan (CS) in promoting wound healing can be attributed to their ability to stimulate collagen production. Among the herbal agents with fewer adverse effects, Tragopogon graminifolius DC. [Asteraceae] (TG), also called “Sheng” in traditional Iranian medicine, is one of the most efficacious plants for treating various skin injuries due to its several pharmacological and biological effects like anti-inflammatory and antioxidant properties.PurposeIn the present study, our objective was to assess the wound-healing activity of PVA/PEO/CS nanofibers containing TG in a rat model of excision wound repair.MethodsSynthesized nanofibers from PVA, PEO, and CS were done by the electrospinning method and confirmed by scanning electron microscopy (SEM) and Fourier-transform infrared spectroscopy (FT-IR). The release tests of nanofibers were assessed through the UV-visible method at different time intervals, which were conducted for about 60 h. To evaluate the wound healing effects, rats were divided into four distinct groups, including negative control (untreated), phenytoin cream (as positive control), polymer (PVA/PEO/CS), and drug (nanofiber-containing 50% of TG extract; named PVA/PEO/CS/TG) groups. All treatments were administered topically once daily for 14 days. Wound size changes were investigated in different time intervals. On the 15th day, nitrite and catalase serum levels were measured. Furthermore, samples of skin tissue were extracted and subjected to histopathological analysis.ResultsPVA/PEO/CS nanofibers containing 1.2 g of PVA, 0.3 g of PEO, and 0.8 g of CS, along with 50% of TG extract (PVA/PEO/CS/TG) at 17 kV were selected based on its favorable morphology and uniform quality. PVA/PEO/CS/TG represented a notable reduction in wound sizes. Moreover, in histopathological analysis, PVA/PEO/CS/TG showed a lower presence of inflammatory cells, higher density of dermis collagen fibers, and better regeneration of the epidemic layer. In addition, PVA/PEO/CS/TG elevated plasma antioxidant capacity via increasing catalase while reducing nitrite levels.ConclusionPVA/PEO/CS/TG is a promising wound dressing nanofiber with antioxidant and tissue regeneration potential. These results encourage further studies for the development of TG nanofibers as promising agents in treating and accelerating the process of excision wound repair.